2017
DOI: 10.1063/1.4986759
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the size of ZnO nanorods on SiO2 substrates by incorporating reduced graphene oxide into the seed layer solution

Abstract: The confinement effect in spherical inhomogeneous quantum dots and stability of excitons AIP Advances 7, 065112 (2017); https://doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In line with the Raman analysis, XRD results also reveal that the crystalline structures of ZnS for the ZnO/ZnS core shell structure 14,15 with the seed layer electrodeposition time of 5 s had stronger both c-axis growth (002) 22 ZnO crystalline structures 23,24 and (111) 25 ZnS cubic structures than all the other samples as shown in Fig. 5.…”
Section: Resultssupporting
confidence: 72%
“…In line with the Raman analysis, XRD results also reveal that the crystalline structures of ZnS for the ZnO/ZnS core shell structure 14,15 with the seed layer electrodeposition time of 5 s had stronger both c-axis growth (002) 22 ZnO crystalline structures 23,24 and (111) 25 ZnS cubic structures than all the other samples as shown in Fig. 5.…”
Section: Resultssupporting
confidence: 72%
“…The rGO in the ZnO seed could enhance the growth of ZnO NRs in the c-plane and inhibit the lateral growth. The ZnO structure has two polar planes, namely, (002) and (00-2), and a charged surface that could cause a faster growth rate along the (002) direction; additionally, rGO enhances the reaction with OH and a Znterminated c-plane [15]. The results of the material analyses indicate that the diameter of ZnO NRs can be effectively modulated by adjusting the rGO compositions, which may have the potential to optimize the ZnO NRs according to the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [12] reported that seed layer and precursor concentration can change the morphology of ZnO NRs. Recently, some researchers have made efforts to control ZnO nanostructures by putting different elements such as polyethyleneimine molecules, surfactants, and graphene-related materials into growth solutions or into the seed layer [13][14][15]. Yu et al [15] and Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI.…”
Section: Introductionmentioning
confidence: 99%